THE APPROPRIATE TECHNIQUE IN ENHANCING STUDENTS’ CAPABILITY IN SPEAKING ENGLISH - Gusti Milla Quaidy; Haykal Alpard (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2018)
Currently, learning English cannot be separated from the classroom process. By learning English, students will be easier to communicate and compete to other students over the world. It happens because English has been existing as the international language used by almost whole people in the world. Related to learn English, there are four skills in English, they are listening, speaking, reading and writing. By considering those skills, speaking is the skill that shows the product during learning English. Unfortunately, numbers of students are lazy to speak because of the anxiety. The anxiety can set the students being unconfident to produce their oral communication. According to Hammer Communicative Language Teaching (CLT) is the name which was given to a set of beliefs which included not only about what aspects of language to teach, but also a shift in emphasis in how to teach. based on the expert findings. Therefore, this paper is proposed to resolve the problem happened by giving the appropriate technique to this case.